Predictors of behavioural intention in the use of the internet by home economics teachers in Malaysia - Phua, Peng Lin; Wong, Su Luan; Abu, Rosini; Soo, Wee Leng (Asian Regional Association for Home Economics, 2016)
This study was aimed at identifying the best predictors of behavioral intention in Internet usage by Home Economics (HE) teachers who taught Integrated Living Skills (ILS). The study cohort comprised 135 HE teachers sampled from a population of 799. Multiple linear regression analysis showed that perceived enjoyment and attitude were the predictors of behavioral intention towards Internet usage, the two factors together explaining 63.1% (adjusted R2=.631) of the variance in HE teachers’ inclination to use the Internet. Between these two predictors, attitude provided a greater unique contribution to the variation in HE teachers’ intention to use the Internet for teaching and learning. Nevertheless, differences in perceived enjoyment triggered greater corresponding changes in behavioral intent to use the Internet.